The Role of Tumor Necrosis Factor in Manipulating the Immunological Response of Tumor Microenvironment - Laha, Dipranjan; Grant, Robert; Mishra, Prachi; Nilubol, Naris (Frontiers in Immunology, 2021)
The tumor microenvironment (TME) is an intricate system within solid neoplasms. In this review, we aim to provide an updated insight into the TME with a focus on the effects of tumor necrosis factor-α (TNF-α) on its various components and the use of TNF-α to improve the efficiency of drug delivery. The TME comprises the supporting structure of the tumor, such as its extracellular matrix and vasculature. In addition to cancer cells and cancer stem cells, the TME contains various other cell types, including pericytes, tumor-associated fibroblasts, smooth muscle cells, and immune cells. These cells produce signaling molecules such as growth factors, cytokines, hormones, and extracellular matrix proteins. This review summarizes the intricate balance between pro-oncogenic and tumor-suppressive functions that various non-tumor cells within the TME exert. We focused on the interaction between tumor cells and immune cells in the TME that plays an essential role in regulating the immune response, tumorigenesis, invasion, and metastasis. The multifunctional cytokine, TNF-α, plays essential roles in diverse cellular events within the TME. The uses of TNF-α in cancer treatment and to facilitate cancer drug delivery are discussed. The effects of TNF-α on tumor neovasculature and tumor interstitial fluid pressure that improve treatment efficacy are summarized.